Unraveling the levels of emerging contaminants along the eastern Mediterranean Sea - Fatima Haydous; Bilal Nehmeh; Joseph Rebehmed; Josephine Al-Alam; Christopher Saab; Sara Sabbagh; Ali Hamieh; Ali Yassin; Mahmoud Wazne; Elias Akoury (Scientific Reports)
Abstract The Eastern Mediterranean Sea, rich in environmental and cultural heritage, faces increasing threats from emerging contaminants like toxic metals and phthalates. This study evaluates their occurrence across 40 Lebanese Mediterranean coastal hotspots using advanced techniques such as Inductively Coupled Plasma Mass Spectrometry (ICP-MS), X-ray Fluorescence Spectroscopy (XRF) and Gas Chromatography-Mass Spectrometry (GC–MS). Widespread contamination was detected in both water and sediments near landfills, sewage discharges, and industrial areas. Metal concentrations varied, with chromium (Cr) reaching 20.3 µg/L, arsenic (As) 12.1 µg/L, and lead (Pb) 30.6 µg/L, indicating pollution from urban and industrial activities. Manganese (Mn) and zinc (Zn) were within safe limits, while selenium (Se) and arsenic posed ecological risks. Among 13 phthalates, diethylhexyl phthalate (DEHP) was the most prevalent, ranging from 15.57 to 72.88 µg/L. Sediments showed elevated calcium, strontium, and barium levels, exceeding safety thresholds. Statistical analysis revealed correlations between contaminants and spatial variability driven by industrial, agricultural, and urban activities. These findings highlight the need for proper regulations and routine monitoring to protect marine ecosystems and public health.